Lexical frequency and morphosyntactic variation: Evidence from U.S. Spanish - Bayley, Robert; Greer, Kristen A.; Holland, Cory L. (Spanish in context, 2017)
The role of frequency in language variation has received a great deal of attention in recent years, especially in phonology. Recently, Erker and Guy (2012) extended the analysis of frequency to morphosyntactic variation and examined frequency effects in variation between null and overt subject personal pronouns (SPPs) in New York City Spanish. Their results suggest that frequency activates or amplifies the effects of other influences on speakers’ choices between overt and null pronouns, such as person and number. Here we attempt to replicate their study. Analysis of more than 8,600 examples of possible sites of SPP variation collected from Mexican immigrant and Mexican American Spanish shows that frequency has only a small effect on a speaker’s choice between an overt and a null pronoun. The results presented here suggest that factors such as a change in reference from the subject of the preceding tensed verb or the person and number of the verb operate independently of frequency effects and provide a better explanation of observed patterns of variation than frequency.